A New Measure of Economic Distance - Eric O'N. Fisher; John Gilbert; Kathryn G. Marshall; Reza Oladi (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper defines a new measure of economic distance. Using consistent cross-country data, we estimate local unit costs for 35 sectors in 40 countries. The distance between two countries is the largest percentage difference in unit costs among all sectors. If all goods are traded, this distance is the smallest uniform ad valorem tariff that shuts down bilateral trade. The network induced by the closest 10% of these distances has one large component, consisting primarily of the advanced industrial economies. China, India, and several other countries are isolated components, indicating that their unit costs are idiosyncratic. We also introduce a new measure of revealed comparative advantage.
Keywords: F10; 330; economic distance; international trade